The Silent Heart: Unveiling Mitral Stenosis in the Postoperative Period - Aparna Bagle; Rashmi Kelkar (Journal of Clinical and Diagnostic Research)
Mitral Stenosis (MS) is a valvular heart condition marked by the narrowing of the mitral valve opening. The normal mitral valve area is 4-6 sq cm [1]. While rheumatic fever is the most common cause, the stenosis generally does not become clinically important until several decades after the initial infection [2]. It usually manifests 20 to 40 years after an episode of rheumatic fever and is more common in females [3]. Common symptoms include orthopnea and paroxysmal nocturnal dyspnea [4]. As the condition progresses, patients may also experience palpitations, chest pain, hemoptysis, and thromboembolism, particularly with an increased left atrial volume.